Effect of cascading amplification stages on the performance of serial hybrid fiber amplifier - Ali M.H.; Abdullah F.; Jamaludin M.Z.; Al-Mansoori M.H.; Abass A.K.; Al-Mashhadani T.F. (Bellwether Publishing, Ltd., 2023)
Brillouin scattering; Broadband amplifiers; Fibers; Noise figure; Raman scattering; Stimulated Brillouin scattering; Experimental validations; Flat-gain; Gain saturation; Hybrid amplifier; Hybrid fiber amplifier; Input signal power; Raman amplifier; Wide-band; Erbium doped fiber amplifiers